PIVOT SYSTEM IN ARABIC COORDINATION SENTENCE: A SYNTACTIC TYPOLOGY STUDY - Mubshirah, Dara; Mulyadi, Mulyadi (Premise: Journal of English Education and Applied Linguistics, 2024)
Coordination sentences are those that operate effectively in both written and spoken discourse. The pivot system will discuss the Arabic coordination sentence in this research. This study aimed to highlight the syntactic typology and pivot system of the Arabic coordination sentence. This study used a qualitative approach with descriptive and content analysis methods. This data was analyzed using the Miles and Huberman method. The data were obtained from the form of coordination sentences found in Arabic books and other sources that are considered relevant. The result showed that the Arabic coordinating sentences are formed by four types, namely (1) intransitive-intransitive, (2) intransitive-transitive, (3) transitive-intransitive, and (4) transitive-transitive. Eliminating FN for A and P in Arabic coordinating sentences differs from dropping FN for A and P in English and Arabic coordinating sentences. However, based on the syntactic constructions with indefinite verbs, Arabic grammar is the same as English and Indonesian. The findings of this study contribute insight and treasure to the wealth of science in syntactic typology.